Pharmacokinetic Profile of Meropenem, Administered at 500 Milligrams Every 8 Hours, in Plasma and Cantharidin-Induced Skin Blister Fluid - Maglio, Dana (American Society for Microbiology, 2003)
The pharmacokinetic disposition of meropenem, administered at 500 mg every 8 h, in plasma and cantharidin-induced blister fluid is described. Peak meropenem concentrations in blister fluid lagged behind peak meropenem concentrations in plasma, while a lower elimination rate from blister fluid was also noted. The mean penetration of meropenem into blister fluid was 67%. The pharmacokinetic profile of meropenem in blister fluid supports the utility of this dose in the management of skin and soft tissue infections.